Enhancing The Awareness of Mechanization Adoption in Agriculture Through Game-Based Learning - Handayati, Yuanita; Putranto, Nur Arief Rahmatsyah; Ardhito, Himawan Nur (SBM ITB, 2021)
Abstract. This research implements game-based learning to build rice farmers' awareness of the importance of using mechanization or advanced technology in agriculture. The use of mechanization is one way to increase farming productivity and efficiency, improve the quality and added value of products, and empower farmers. This study examines farmers' attitudes towards the adoption of mechanized methods and proposes a suitable game-based learning approach. First, qualitative methods were employed to develop the game by gathering information, pilot testing, and asking for feedback from farmers. Then, the quantitative method is applied to assess the game's effectiveness using a post- and pretest questionnaire. Cluster analysis was also conducted to determine the proper learning approach based on the farmers' characteristics. The game-based approach is shown to shed light on fostering the adoption of mechanized methods. There are two clusters identified. On average, the first cluster has a younger age, higher educational background, and more positive attitudes toward using mechanized methods. The second cluster, on average, has an older age, a lower educational level, and lower scores in their attitudes toward the adoption of mechanization. The findings also suggest that the farmers in the first cluster may be reached using a pedagogy-based approach, whereas the second is likely to be more receptive to an andragogy-based approach.Keywords: Agriculture; rice farmers; mechanization method; game-based learning; learning approachAbstrak. Penelitian ini menerapkan pembelajaran berbasis permainan untuk membangun kesadaran petani padi akan pentingnya menggunakan teknik mekanisasi dalam pengelolaan lahannya. Selain itu, penelitian ini mengkaji sikap petani terhadap adopsi metode mekanisasi dan mengusulkan pendekatan pembelajaran yang sesuai dengan karakteristik petani. Pertama, metode kualitatif digunakan untuk mengembangkan permainan dengan mengumpulkan informasi, melakukan uji coba, dan meminta umpan balik dari petani. Kemudian, metode kuantitatif diterapkan untuk menilai keefektifan permainan dengan kuesioner post and pre-test. Analisis klaster juga dilakukan untuk mengetahui pendekatan pembelajaran yang tepat berdasarkan karakteristik petani. Pembelajaran berbasis permainan telah terbukti membantu mendorong petani melakukan adopsi metode mekanisasi. Ada dua klaster yang teridentifikasi. Klaster pertama memiliki usia yang lebih muda, latar belakang pendidikan tinggi dan rata-rata memiliki skor sikap menggunakan metode mekanisme yang lebih tinggi. Klaster kedua memiliki usia yang lebih tua, tingkat pendidikan yang lebih rendah juga skor yang lebih rendah dalam sikap mereka terhadap adopsi rata-rata. Hasil penelitian juga menunjukkan bahwa petani di klaster pertama dapat didekati dengan menggunakan pendekatan berbasis pedagogis, sedangkan klaster kedua dapat didekati dengan pendekatan berbasis andragogi.Katakunci: Pertanian; petani padi; metode mekanisasi; pembelajaran berbasis permainan; pendekatan pembelajaran